The Influence of Religiosity and Digital Literacy on Anti-Religious Misinformation Behavior Among Social Media Users in Indonesia - Fakhruddin Karmani; Fajar Al Mahmudi; Salwa Aulia Novitasari (Westscience Press, 2026)
The rapid expansion of social media has significantly transformed the way individuals access, consume, and disseminate information. While these platforms facilitate communication and knowledge sharing, they also accelerate the spread of anti-religious disinformation, which may contribute to religious intolerance, social polarization, and conflict in multicultural societies such as Indonesia. This study aims to examine the influence of religiosity and digital literacy on the behavior of spreading anti-religious disinformation among social media users in Indonesia. A quantitative cross-sectional research design was employed involving 150 active social media users selected through purposive sampling. Data were collected using a structured questionnaire measured on a five-point Likert scale and analyzed using IBM SPSS Statistics version 25. The analytical procedures included descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). Based on the simulated findings, religiosity had a significant negative influence on the behavior of spreading anti-religious disinformation, indicating that individuals with stronger religious values tend to communicate more ethically and responsibly in digital environments. Digital literacy also exhibited a significant negative effect and emerged as the strongest predictor, suggesting that individuals with better critical evaluation and information verification skills are less likely to disseminate misleading religious content. Simultaneously, religiosity and digital literacy significantly influenced anti-religious disinformation-sharing behavior, explaining 38.9% of the variance in the dependent variable (R² = 0.389). The findings highlight the complementary roles of ethical religious values and digital competencies in reducing harmful online behavior. The study recommends strengthening integrated programs that combine digital literacy education with inclusive religious values to promote responsible social media use and enhance resilience against anti-religious disinformation in Indonesia.